2015
DOI: 10.1371/journal.pone.0133718
|View full text |Cite
|
Sign up to set email alerts
|

Is Mandatory Prospective Trial Registration Working to Prevent Publication of Unregistered Trials and Selective Outcome Reporting? An Observational Study of Five Psychiatry Journals That Mandate Prospective Clinical Trial Registration

Abstract: ObjectiveTo address the bias occurring in the medical literature associated with selective outcome reporting, in 2005, the International Committee of Medical Journal Editors (ICMJE) introduced mandatory trial registration guidelines and member journals required prospective registration of trials prior to patient enrolment as a condition of publication. No research has examined whether these guidelines are impacting psychiatry publications. Our objectives were to determine the extent to which articles published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 27 publications
7
77
2
Order By: Relevance
“…Although no direct mechanism exists for identifying unregistered trials systematically, late registrations are a marker that stakeholders enable trials to proceed without prospective registration. 19,24 …”
Section: Assessing Clinicaltrialsgov and The Evolving Trsmentioning
confidence: 99%
“…Although no direct mechanism exists for identifying unregistered trials systematically, late registrations are a marker that stakeholders enable trials to proceed without prospective registration. 19,24 …”
Section: Assessing Clinicaltrialsgov and The Evolving Trsmentioning
confidence: 99%
“…In a review of five psychiatry journals that mandate registering of prospective clinical trials, it was reported that only 33% of trials were correctly prospectively registered and, of these, 28% had evidence of selective outcome reporting and 27% a large change in participant numbers. Overall, only 14.4% were correctly registered and reported 7. For psychotherapy RCTs, the results were even worse.…”
Section: ‘It-work-somewhere’mentioning
confidence: 92%
“…As noted below, a system of prospective registration of clinical trials is in place to combat this issue. However, data suggest that the toptier psychiatric journals still allow changes in registered primary outcomes without this being highlighted in the paper (Scott et al, 2015). Outside the area of randomised control trials, there is little in place to avoid this problem.…”
Section: Other Ways In Which Negative Findings Are Minimisedmentioning
confidence: 99%